2021
DOI: 10.1038/s41598-020-79866-y
|View full text |Cite|
|
Sign up to set email alerts
|

Aortic acceleration as a noninvasive index of left ventricular contractility in the mouse

Abstract: The maximum value of the first derivative of the invasively measured left ventricular (LV) pressure (+ dP/dtmax or P′) is often used to quantify LV contractility, which in mice is limited to a single terminal study. Thus, determination of P′ in mouse longitudinal/serial studies requires a group of mice at each desired time point resulting in “pseudo” serial measurements. Alternatively, a noninvasive surrogate for P′ will allow for repeated measurements on the same group of mice, thereby minimizing physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…This catheter can measure the maximal rate of rise of left ventricular pressure (LV dP/dtmax). This parameter is widely used to assess contractility in several species [ 39 , 40 , 41 ]. The effects of pimobendan on inotropism appear less pronounced in anaesthetised dogs than in awake dogs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This catheter can measure the maximal rate of rise of left ventricular pressure (LV dP/dtmax). This parameter is widely used to assess contractility in several species [ 39 , 40 , 41 ]. The effects of pimobendan on inotropism appear less pronounced in anaesthetised dogs than in awake dogs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, PV and MA were used to assess changes in inotropism: PV is the maximum velocity of blood in the aorta, and MA is the slope of the aortic velocity curve. These two parameters have previously been used to assess cardiac inotropism and have proven to be good indicators of a range of contractility situations in humans, mice, and dogs [ 39 , 40 , 41 ]. PV and MA reasonably correlate with LV dP/dtmax [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitral regurgitation (MR) has not been well-described in mice because of their resistance to developing mitral valve prolapse ( 11 ). However, Li et al recently reported the first mouse model of severe MR ( Figure 11 , 12 ).…”
Section: Materials and Equipmentmentioning
confidence: 99%